DAYA HIDUP SPERMATOZOA KAMBING PERANAKAN ETAWA YANG DIPRESERVASI DENGAN BERBAGAI JENIS PENGENCER - Muhammad Rizal; Muhammad Thahir (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2016)
The purpose of this research was to examine the effectivity of Tris, sodium citrate, and lactose extenders in maintaining viability of etawa crossbreed (EC) goat spermatozoa preserved at 3–5oC.  Semen was collected using artificial vagina once a week for six times as replicate.  Fresh semen was divided into three tubes then diluted with Tris, sodium citrate, and lactose extenders, respectively.  Diluted-semen were stored in refrigerator at 3–5oC.  Quality of diluted-semen including percentages of motile spermatozoa (MS) and live spermatozoa (LS) were evaluated every day during storage at 3–5oC for four days.  Data were analyzed using completely randomized design with three treatments and six replicates.  Results of this study showed that mean volume, colour, consistency, pH, mass activity, spermatozoa concentration, MS, LS, and spermatozoa abnormal of PE goat fresh semen were 1.05 ml, cream, thick, 6.9, ++ – +++, 3,756.67 million cell/ml, 76.67%, 85.83%, and 4.5%, respectively.  Tris, sodium citrate, and lactose extenders have same ability in maintaining viability of EC goat spermatozoa during preserved at 3–5oC.  At day-4 storage, percentages of MS and LS for Tris (44.17 and 57.83%) was no difference significant with sodium citrate (43.33 and 56.67%), and lactose (43.33 and 54.17%).   In conclusion, Tris, sodium citrate, and lactose extenders have same ability in maintaining viability of EC goat spermatozoa during preserved at 3–5oC.  Tris, sodium citrate, and lactose extenders could be maintaining 40% in percentage of motile spermatozoa for three days after preserved at 3–5oC, and suitable for use in artificial insemination (AI) programKeywords: Tris, sodium citrate, lactose, spermatozoa viability, PE goat.